The suburban church : modernism and community in postwar America - Buggeln, Gretchen Townsend (Architecture, landscape, and American culture series., 2015)
"After World War II, America's religious denominations spent billions on church architecture as they spread into the suburbs. In this richly illustrated history of midcentury modern churches in the Midwest, Gretchen Buggeln shows how architects and suburban congregations joined forces to work out a vision of how modernist churches might help reinvigorate Protestant worship and community. The result is a fascinating new perspective on postwar architecture, religion, and society. Drawing on the architectural record, church archives, and oral histories, The Suburban Church focuses on collaborations between architects Edward D. Dart, Edward A. Sovik, Charles E. Stade, and seventy-five congregations. By telling the stories behind their modernist churches, the book describes how the buildings both reflected and shaped developments in postwar religion--its ecumenism, optimism, and liturgical innovation, as well as its fears about staying relevant during a time of vast cultural, social, and demographic change. While many scholars have characterized these congregations as "country club" churches, The Suburban Church argues that most were earnest, well-intentioned religious communities caught between the desire to serve God and the demands of a suburban milieu in which serving middle-class families required most of their material and spiritual resources."--